Highly efficient blue emissive copper halide Cs5Cu3Cl6I2 scintillators for X-ray detection and imaging. Issue 20 (15th October 2022) - Niu, Xiaowei; Xiao, Jiawen; Lou, Bibo; Yan, Zhengguang; Zhou, Quan; Lin, Taifeng; Ma, Chonggeng; Han, Xiaodong
Abstract: In recent years, copper-based halide scintillators have attracted tremendous attention due to their excellent luminescent properties and low manufacturing costs. Herein, a high-performance and low-cost Cs5 Cu3 Cl6 I2 scintillator is prepared by simple mechanical grinding. The mixed-halide Cs5 Cu3 Cl6 I2 phosphor exhibits a blue emission centered at 475 nm with a large stokes shift, originating from the self-trapped exciton emission of Cu sites. The photoluminescence quantum yield (PLQY) of Cs5 Cu3 Cl6 I2 can be increased to 88.4% from 20.4% by the efficient suppression of the anion vacancy defects. In addition, the Cs5 Cu3 Cl6 I2 scintillator shows a high steady-state X-ray to light conversion efficiency of about 57000 photons/MeV, good X-ray linear response, and low detection limit of 71.9 nGyair /s. The X-ray imaging results based on the Cs5 Cu3 Cl6 I2 scintillator screen display a high spatial resolution of 9.0 line-pairs per millimeter (lp/mm). Furthermore, Cs5 Cu3 Cl6 I2 exhibits good radiation stability under a total dose of 113.58 Gyair . Overall, the Cs5 Cu3 Cl6 I2 scintillator prepared by mechanical grinding method has the advantages of low cost, high efficiency, and good radiation resistance, suggesting its huge potential in X-ray detection and imaging.